1990
DOI: 10.1016/0167-5729(90)90002-u
|View full text |Cite
|
Sign up to set email alerts
|

Photoemission studies of high-temperature superconductors

Abstract: Photoemission studies have been performed on all classes of high temperature superconductors except the Tl-related compounds. Particular attention was paid to the surface cleanliness. Comparison with band calculation shows that the one-electron picture cannot adequately explain the electronic structure of this type of materials. Most important, Cu satellites were observed both in the valence band and the Cu 2p core level for all the samples studied, signaling the importance of the d-d correlation effects. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(19 citation statements)
references
References 220 publications
3
14
0
Order By: Relevance
“…High-energy spectroscopy techniques, especially polarized x-ray absorption measurements, have been widely used in probing the electronic states near the Fermi level in these rather complex materials [1,2]. In particular, a number of polarized x-ray absorption spectroscopy (XAS) and electron energy loss spectroscopy (EELS) studies have been made to obtain valuable information on the symmetry of unoccupied states in the normal state [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], and to understand the behaviour of holes in the superconducting state [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…High-energy spectroscopy techniques, especially polarized x-ray absorption measurements, have been widely used in probing the electronic states near the Fermi level in these rather complex materials [1,2]. In particular, a number of polarized x-ray absorption spectroscopy (XAS) and electron energy loss spectroscopy (EELS) studies have been made to obtain valuable information on the symmetry of unoccupied states in the normal state [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], and to understand the behaviour of holes in the superconducting state [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…1 shows partially angle-integrated energy distribution curve (EDC) of the as-transferred specimens. Two features are noteworthy: the absence of a "dirt" peak around 9 eV [20], and the presence of a clear Fermi edge, both indicating that the sample surface prepared in our method is free from contamination and suitable for ARPES investigation of the low-energy electronic structure. Our preliminary experiments on hν dependence (25 -50 eV) indicated that the structure near Fermi energy (E F ) is prominent for ~50 eV photons, so the following ARPES data were obtained using 50 eV photons.…”
Section: Methodsmentioning
confidence: 99%
“…In YBa 2 Cu 3 O 7Ϫ␦ ͑Y123͒ and La214, this peak has been attributed to an oxygen vacancy at the surface. 14 Figure 2 shows the spectra around the valence band in sample C, which is almost optimally doped, with different light sources. Although there is a peak at 9 eV in all spectra, we believe that this peak originates from the Hg 5d state for the following reasons.…”
Section: A Confirmation Of the Intrinsic Surfacementioning
confidence: 99%
“…Instead, we turned our attention to the peaks below 5 eV. In La214 and Y123, the spectra for the surface deteriorated samples show a larger intensity at 4-5 eV than the intensity near 3 eV in lower light source energy such as UPS, 14 because the vacant oxygen creates peaks at 4-5 eV. As shown in Fig.…”
Section: A Confirmation Of the Intrinsic Surfacementioning
confidence: 99%